FAKTOR ORANG TUA TIDAK MENYEKOLAHKAN ANAKNYA KEJENJANG YANG LEBIH TINGGI DI DESA BINUANG KECAMATAN BANGKINANG - ', Masgawati; Irja, Desti; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research it is based on factors some parents do not send their children to higher degrees in the village Binuang Kecamatan Bangkinang Seen from the parents are send their children to school. Factors some parents do not send their children to higher degrees in the village Binuang Kecamatan Bangkinang Seen from the education, the economic and the community. What factors some parents do not send their children to higher degrees in the village Binuang Kecamatan Bangkinang?. So the purpose this study is to some parents do not send their children to higher degrees in the village Binuang Kecamatan Bangkinang. And, research is expected to become guidelines for older people in send their children to school. The research also is expected to help and loosening take actions repair to next, for parents to send their children. Population in this study as many as 50 people. Then the researcher take intended to the sample 30 people for research and 20 people we will try to, with uses the technique of sampling jenuh. An instrument data collection namely poll with 40 a statement and if the trial live 37 a statement that valid to make instrument in research. Through data analysis of the quantitative descriptive analysis. So, a conclusion can be drawn that, some parents do not send their children to higher degrees in the village Binuang Kecamatan Bangkinang within high. Indicators the community higher than indicators the education level of parents and the level economic.Key words: Factor, factors some parents do not send their children to school